PERANCANGAN SISTEM INFORMASI MANAJEMEN LAYANAN PEMINJAMAN ALAT PERTANIAN BERBASIS WEB MENGGUNAKAN FRAMEWORK ITIL PADA DINAS PERTANIAN - yusuf, nabila; Pramesti Putri, Andara; Dewi Tomayahu, Cindera; Ulhaq Tuloli, Muh. Dhiya; Musaqina Mue, Syabila; Muktadilah Benawan, Moh Ihsan (TRANSFORMASI, 2026)
The lending service for agricultural tools and machinery at the Department of Agriculture is still managed manually, causing data recording errors, unclear equipment availability, low transparency, and delayed reporting. This study designs a web-based Agricultural Equipment Lending Service Management Information System using the Information Technology Infrastructure Library (ITIL) framework through five domains: Service Strategy, Service Design, Service Transition, Service Operation, and Continual Service Improvement. System development uses the Waterfall method with data collected through observation and interviews. The resulting system supports equipment inventory management, digital loan submission, real-time status monitoring, and automated reporting. System testing was conducted using the System Usability Scale (SUS) method, obtaining an average score of 75.83, which falls into the “OK” (Grade C) category according to Bangor et al. (2008), indicating that the system has a fairly good level of usability and is acceptable to users. ITIL implementation ensures more structured, transparent, and sustainable services at the Department of Agriculture. Keywords: IT Service Management, ITIL, Lending System, Management Information System, Public Service